Integrated Nutrient Management Technology forKamalam Fruit Cultivation - Das, Biswajit; Devi, H Lembisana; Das, Bapi; Devi, A G; Singh, Vinay; Sarkar, Pradip; Baidya, Ashima Suklay (Indian Horticulture, 2024)
Dragon fruit or Kamalam (Hylocereus spp.) has been considered as a potential fruit crop in India. Application of fertilizer in several split doses at specific plant growth stages is important considering its shallow root system, continuous luxurious growth habit of flashy stems, heavy bearing nature, and loss of applied fertilizes due to high rainfall. The paper discusses the planting methods and integrated nutrient management for the cultivation of Kamalam fruit.